Knowledge, Awareness and Expectations of Root Canal Treatment: Patients’ Perspective - Gautam, Suman; Thapa, Asha; Joshi, Rojin; Joshi, Barsha; Joshi, Barsha; Karmacharya, Aakash (Nepal Medical College Journal, 2022)
Root canal treatment (RCT) is one of the common procedures done in order to retain the natural tooth and avoid extraction. The major reason for patient not opting for RCT is due to lack of knowledge. The factors that discourage the patient and hinder the treatment when identified will help the understanding of the clinician to adequately address the issue. Thus, this study with aim to assess the knowledge, awareness and expectation of RCT from patients’ perspective was undertaken. This survey was conducted with pre-structured questionnaire consisting of 13 questions and were distributed to random 404 patients attending the department. The completed questionnaire was the analyzed. 61.4 % of participants had knowledge of RCT. Participants with previous experience of RCT were more likely to undertake the procedure again despite the cost issue, when required, then those who had no previous experience.72% of the participants choose specialized service. In comparison to other studies the knowledge and awareness regarding RCT was higher in this study.